TINJAUAN HUKUM ISLAM TENTANG PENYEBAB BERPINDAHNYA WALI NASAB KEPADA WALI HAKIM DI KUA KECAMATAN BULU - Wibowo, Andi; Syamsudin, S; Baehaqi, B (AL HUKMU: Journal of Islamic Law and Economics, 2024)
The main problem in this research is, What Causes the Transfer of Guardians of Nasab to Guardians of Judges in KUA Bulu District and How the Views of Islamic Law Against Marriage Implementation With Guardians of Judges in KUA  Bulu District. This type of research used in research is oKualitatif, is the involvement of an object with the aim to understand the knowledge of an event based on knowledge with ideas that have been previously known. While based on its descriptive analytic nature, it is a method that serves to provide a description of the object under study through data or samples that have been collected as it is without performing analysis and making conclusions that are generally accepted. The cause of the transfer of the line guardian to the guardian of the lineage at the KUA Bulu District, there are several factors that cause the transfer of the line guardian to the guardian of the judge in marriage, namely because the guardian of the line is not there, the guardian of the line is adhal, the guardian of the line is not known or unseen, the guardian of the lineage is convicted, the guardian of the lineage is not Muslim, and the guardian of the lineage who will marry himself will get married. The view of Islamic law on the implementation of marriage with the guardian of the judge at KUA Kecamatan Bulu District, in carrying out a marriage using a guardian judge is considered valid as long as the terms and conditions apply.